Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran - Hajiesmaeilian, Abolfazl; Shoushtari, Reza Vafaei; Mozaffarian, Fariba; Ebrahimi, Ebrahim (Zootaxa, 2020)
During a study of the family Myrmeleontidae of Iran, specimens of the tribe Myrmeleontini, housed in Hayk Mirzayans Insect Museum were examined. Specimens of Euroleon nostras and Myrmeleon noacki were identified for the first time from Iran. An identification key, illustrations and distributional maps are presented for the Iranian species of Myrmeleontini.